Synergy Between Pharmacy and Laboratory: Enhancing Patient Care and Outcomes - Alrumayyan, Bashayer Firas Mohammed; Abandi, Makiah Ali; Al-Qahtani, Basmah Fahad; alotaibi, Khaled Jameel; alotaibi, Asma Dhawi; Alatyah, Yasmin Wasel; MOTMY, ALI AHMED YAHYA (Journal of Ecohumanism, 2024)
The healthcare landscape is rapidly evolving, with an increasing emphasis on integrated and patient-centered care. Within this context, pharmacy and laboratory services play crucial and often complementary roles in enhancing patient care and optimizing health outcomes. Pharmacy and laboratory professions rely on similar values, principles, and processes, although they have developed unique characteristics and functions. In an effort to promote collaboration between these two fields, a research was conducted to explore the synergy between pharmacy and laboratory services regarding patient care. It begins by examining current pharmacy and laboratory practices in enhancing patient care and health outcomes. From this examination, potential areas for improved collaboration and synergy are identified (Strain & H. Ravalico, 2021). A survey was conducted with the laboratory professionals and pharmacy professionals to gather input regarding the current practices of laboratories and pharmacies in patient care, health outcome improvement initiatives, and collaborative efforts. The qualitative data obtained from these free-text responses were analyzed using the constant comparative method to identify common themes and categories. The findings are then discussed within the context of relevant literature, highlighting the implications of the input with regard to the patient care and health outcome improvement initiatives of pharmacy and laboratory services. Finally, suggestions for enhancing collaboration and synergy are presented (John et al., 2023).